Factors related to mammography adherence among women in Brazil: A scoping review - Camila Brasil Moreira; V. Susan Dahinten; A. Fuchsia Howard; Ana Fátima Carvalho Fernandes; Janine Schirmer (Wiley, 2021)
Abstract Aim To explore and synthesize the literature on factors related to mammography screening adherence among women in Brazil. Design A scoping review. Methods We searched 11 databases for studies published between 2006-January 2020. All identified articles were screened, and data were extracted from eligible studies. We used the UK Government Social Research Service weight of evidence appraisal tool to appraise the quality of the included study. Results From a total of 1,384 identified articles, 22 were retained. All included studies used quantitative, non‐experimental methods and all but two studies used cross‐sectional data. Quality of evidence varied across studies. We identified 41 factors that were investigated across the set of studies. Demographic and socio‐economic factors were the most commonly investigated, with older age, urban residence, living in the southeast of Brazil, higher level of education, higher income and private health insurance most consistently associated with mammography adherence.